Small and Medium Scale Enterprises and their Role in Employment Generation in Nepal - Khatri, Mukti Bahadur (Tribhuvan University Journal, 2020)
SMEs have historically played an important role in contributing to employment generation of many countries around the world. Naturally all businesses start as small businesses or even start out of small businesses initiated by individuals. It is imperative to give high priority to Nepalese labor, skill and raw material based domestic investments to promote national level industries for achieving employment. This study has used regression analysis to investigate relative changes in the position of the Nepalese small and medium scale enterprises (SME’s) to the employment between the time period 2046 and 2073 based on secondary data. It has examine the dynamic relationship among the SMEs and employment in Nepal and found to be significant and positive relationship in between SMEs and employment of Nepal. It implies that number of employment was seemed to be mostly influenced by number of SMEs. However it was and still is contributing significant role in employment generation in Nepal.